PENGARUH PENAWARAN HARGA DAN LOKASI TERHADAP MINAT BELI RUMAH PADA E-LAGOON TOWNHOUSE KOTA TANGERANG SELATAN - Mohamad Andrian Okdiansyah; Kiki Dwi Wijayanti (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of price and location both partially and simultaneously on buying interest in E-Lagoon Townhouse South Tangerang City. This type of research uses a quantitative approach with associative methods. The population in this study were 80 people. By using saturated sampling, the entire population is used as a sample because the population is below 100 so that the sample is 80 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient on determination, and hypothesis testing. The results of the study showed that price has a significant effect on buying interest with a coefficient of determination of 0.98% and hypothesis testing tcount > ttable or (2.912 > 1.990). location has a significant effect on buying interest with a coefficient of determination of 42% and hypothesis testing tcount > ttable or (7.514 > 1.990). price and location simultaneously have a significant effect on buying interest with the regression equation Y = 11,168 + 0,024X1 + 0,532X2. The coefficient of determination is 42,1%.